2010
DOI: 10.1007/s00101-010-1828-1
|View full text |Cite
|
Sign up to set email alerts
|

Wertigkeit von 5 Kernaspekten der Prämedikationsvisite

Abstract: These results suggest that the integration of a pre-anesthesia assessment clinic in anesthetic patient care is not favorable from the patients' point of view because getting to know the anesthetist who will deliver anesthesia is of paramount importance to most patients. In cases where a pre-anesthetic assessment clinic is indispensable, other measures to build up confidence compensating for the lack of personal patient-physician relationship should be developed. In this respect, the promotion of a corporate id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
4
0
4
Order By: Relevance
“…Nevertheless, those who were seen at the OPAC were three times more likely to both prefer it and pay more than US$13 for this type of care over the conventional approach. Irrespective of where anesthesia consultation takes place, patients in a German study were found to value a close relationship with an anesthesiologist without waiting too long to see them [29]. Of the €100 available to spend, patients were willing to pay €36 for a pre-anesthetic visit performed by the anesthesiologist who would give anesthesia, €26 to wait less than two hours, €16 for preferred location of pre-anaesthetic visit, €12 for multimedia information and €10 for ambience [29].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, those who were seen at the OPAC were three times more likely to both prefer it and pay more than US$13 for this type of care over the conventional approach. Irrespective of where anesthesia consultation takes place, patients in a German study were found to value a close relationship with an anesthesiologist without waiting too long to see them [29]. Of the €100 available to spend, patients were willing to pay €36 for a pre-anesthetic visit performed by the anesthesiologist who would give anesthesia, €26 to wait less than two hours, €16 for preferred location of pre-anaesthetic visit, €12 for multimedia information and €10 for ambience [29].…”
Section: Discussionmentioning
confidence: 99%
“…andernfalls wird er den Wert der Professionalität nicht verstehen und einschätzen können. 1 Wenn Organisator und akteure in der intrinsischen Motivation übereinstimmen und den Organisationszweck teilen, sind sie in einer besonderen Weise miteinander verbunden. indem sie sich einig über den Wert der Professionalität sind, teilen sie einen "Wertkonsens".…”
Section: Die Therapeutische Interaktion Als Moralische Vorgabeunclassified
“…Darin sei essentiell "öffentliches Vertrauen in Ärzte, das von der integrität sowohl der individuellen Ärzte als auch der Profession als ganzer abhängt". 2 Dann statuiert sie drei "fundamentale Prinzipien", nämlich "Vorrangigkeit des Patientenwohls", "Selbstbestimmung des Patienten" und "soziale gerechtigkeit", dazu zehn "professionelle Verantwortlichkeiten", darunter die folgenden drei: (1) "Ärzte müssen sich verpflichtet fühlen, lebenslang zu lernen und verantwortlich dafür zu sein, das medizinische Wissen sowie die klinischen und kollegialen Fertigkeiten aufrechtzuerhalten, die für das erbringen hochwertiger Versorgung (quality care) notwendig sind. Umfassender gesagt, die Profession als ganze muss sich darum bemühen, darauf zu achten, dass alle ihre Mitglieder kompetent sind, und muss sicherstellen, dass geeignete Mechanismen vorhanden sind, damit Ärzte dieses Ziel erreichen können."…”
Section: Die Therapeutische Interaktion Als Moralische Vorgabeunclassified
See 2 more Smart Citations